PENGGUNAAN PERMAINAN KARET GELANG DALAM PEMBELAJARAN MATEMATIKA REALISTIK MATERI BILANGAN: Use Of Rubber Band Games In Learning Realistic Mathematics Number Material - Fauziah, Elfara Putri; Hanafi, Taufiq; Zuliana, Eka (Al-Aqlu: Jurnal Matematika, Teknik dan Sains, 2024)
The purpose of this research is to determine the usefulness and effectiveness of real rubber band games for students in learning realistic mathematics with number material which is carried out on students in class 1 of elementary school or phase A at SD NEGERI 3 SIDIGEDE WELAHAN JEPARA, totaling 15 students so that they can learn mathematics. fun for students. The method used in the research is a qualitative descriptive method using observation and interviews as well as photo and video documentation techniques. The results of the research show that the use of rubber band games can be an effective method in helping grade 1 students to understand mathematical concepts, especially numbers and understanding addition and subtraction, in a fun and interactive way. The findings of the study indicate that the incorporation of rubber band games proves to be a highly effective educational approach for first-grade students. The games contribute significantly to the students' comprehension of mathematical concepts, with a specific emphasis on numbers, as well as fostering a deeper understanding of addition and subtraction operations. The interactive and enjoyable nature of the games ensures an engaging learning experience, demonstrating the potential of real rubber band games as a valuable method in elementary mathematics education.